Evangelización waorani y violencia cultural en el Ecuador: 1956-2024 - Andrade, Susana M. (2025)
This article analyzes the Protestant evangelization process carried out by the Summer Institute of Linguistics among the Waorani of the Ecuadorian Amazon, from the arrival of American missionaries in 1954 to the present. Through oral testimonies, missionary documents, and ethnographic research, it examines the impact of evangelization on the Waorani people. The article argues that, under the discourse of salvation, a civilizing model was imposed that eroded key elements of traditional culture while enabling forms of economic and symbolic dependence. It also warns of the current risk of replicating this process with Indigenous peoples in voluntary isolation, through missions promoted by the evangelized Waorani. The article concludes that Waorani collective memory expresses both the traces of civilizational trauma and resistance to the drive for evangelization and cultural homogenization.